Multilayer ceramic capacitor
Patent Information
- Application Number
- CN202280059867.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-30
- Filing Date
- 2022-09-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-09-27
AI Technical Summary
层叠陶瓷电容器具有交替地层叠了电介质层和内部电极层的构造,起因于被薄层化的高介电常数电介质层,虽然是小型,但却具有大的静电电容
[0022]根据本发明,能够提供一种介电常数高、能够小型化以及大电容化并且介电常数的温度特性平坦且可靠性优异的层叠陶瓷电容器。
Smart Images

Figure CN117916833B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to multilayer ceramic capacitors. Background Technology
[0002] With the miniaturization of electronic devices, such as mobile phones, and the increasing speed of CPUs, the demand for multilayer ceramic capacitors (MLCCs) is growing. MLCCs have a structure that alternately stacks dielectric layers and internal electrode layers. Due to the thinned high-dielectric-constant dielectric layers, they possess large electrostatic capacitance despite their small size. Although various materials are known for their use in MLCCs, those using barium titanate (BaTiO3) compounds for the dielectric layer and base metals such as nickel (Ni) for the internal electrode layer are widely used due to their low cost and high performance.
[0003] For example, in Patent Document 1, a dielectric ceramic composition is described, which includes a dielectric layer used in a multilayer ceramic capacitor, and a conductive material preferably Ni or a Ni alloy contained as an internal electrode layer (claims 1,
[0017] , and
[0039] of Patent Document 1), wherein the dielectric ceramic composition comprises materials that can be formed by the compositional formula (Ba 1-x-y Sr x Ca y ) m (Ti 1- z Zr z The main component is composed of perovskite-type compounds represented by O3, the first subcomponent is composed of oxides of rare earth elements R, the second subcomponent is composed of oxides of Mg, the third subcomponent is composed of oxides of at least one element M selected from Mn, Cr, Co and Fe, and the fourth subcomponent is a sintering aid.
[0004] Prior art literature
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-178686 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] To achieve miniaturization and increased capacitance in multilayer ceramic capacitors, it is crucial to improve the dielectric constant of the dielectric layer and further thin it. However, adjusting the composition of the main components constituting the dielectric layer to increase the dielectric constant tends to lead to greater temperature variations. Large temperature variations in the dielectric constant deteriorate the capacitance-temperature characteristics of the multilayer ceramic capacitor. Furthermore, further thinning the dielectric layer results in a shorter insulation resistance lifetime between the internal electrode layers, leading to decreased reliability. While previous techniques have shown some effectiveness, they have limitations in achieving multilayer ceramic capacitors with high dielectric constants, flat temperature characteristics, and consequently, excellent reliability.
[0009] The present invention was made to solve such previous problems, and its objective is to provide a multilayer ceramic capacitor with high dielectric constant, capable of miniaturization and large capacitance, and with flat temperature characteristics of dielectric constant and excellent reliability.
[0010] Technical solutions for solving the problem
[0011] This invention includes the following methods. Furthermore, in this specification, expressions such as "~" include the numerical values at both ends. That is, "X~Y" is synonymous with "X and above and Y and below".
[0012] According to one aspect of the present invention, a multilayer ceramic capacitor is provided, comprising: a multilayer having a first main surface and a second main surface opposite each other in the thickness direction, a first side surface and a second side surface opposite each other in the width direction, and a first end surface and a second end surface opposite each other in the length direction, and including a plurality of dielectric layers and a plurality of internal electrode layers stacked in the thickness direction; and a pair of external electrodes respectively disposed on the first end surface and the second end surface and connected to the plurality of internal electrode layers, wherein...
[0013] The dielectric layer contains dielectric particles.
[0014] The laminate is divided into:
[0015] A layered first side portion, extending along the first side surface, does not include an internal electrode layer;
[0016] The layered second side extends along the second side and does not include the internal electrode layer;
[0017] The first outer layer is sandwiched between the first side and the second side, and is also sandwiched between the inner electrode layer closest to the first main surface and the first main surface;
[0018] The second outer layer is sandwiched between the first side and the second side, and is also sandwiched between the inner electrode layer closest to the second main surface and the second main surface; and
[0019] The inner layer is sandwiched between the first side and the second side, and is also sandwiched between the first outer layer and the second outer layer.
[0020] In a cross section passing through the center of the length direction of the laminate, the dielectric layer at the center of the thickness direction of the inner layer contains particles with holes as dielectric particles.
[0021] Invention Effects
[0022] According to the present invention, a multilayer ceramic capacitor with high dielectric constant, capable of miniaturization and large capacitance, and having flat temperature characteristics of dielectric constant and excellent reliability can be provided. Attached Figure Description
[0023] Figure 1 This is a three-dimensional view showing the shape of a multilayer ceramic capacitor.
[0024] Figure 2 This is a schematic cross-sectional view showing the internal structure of a multilayer ceramic capacitor.
[0025] Figure 3 This is a schematic cross-sectional view showing the internal structure of a multilayer ceramic capacitor.
[0026] Figure 4 This is a TEM-HAADF image showing a particle with a hole. Detailed Implementation
[0027] Specific embodiments of the present invention (hereinafter referred to as "this embodiment") will be described. However, the present invention is not limited to the following embodiments, and various modifications can be made without changing the spirit of the invention.
[0028] (1) Multilayer ceramic capacitor
[0029] The multilayer ceramic capacitor of this embodiment has a first main surface and a second main surface opposite each other in the thickness direction, a first side surface and a second side surface opposite each other in the width direction, and a first end surface and a second end surface opposite each other in the length direction. This multilayer ceramic capacitor includes: a laminate containing a plurality of dielectric layers and a plurality of internal electrode layers stacked in the thickness direction; and a pair of external electrodes respectively disposed on the first end surface and the second end surface and connected to the plurality of internal electrode layers. The dielectric layers contain dielectric particles. Furthermore, the laminate is divided into: a layered first side portion extending along the first side surface and not including an internal electrode layer; a layered second side portion extending along the second side surface and not including an internal electrode layer; a first outer layer portion sandwiched between the first and second side portions and sandwiched between the internal electrode layer closest to the first main surface and the first main surface; a second outer layer portion sandwiched between the first and second side portions and sandwiched between the internal electrode layer closest to the second main surface and the second main surface; and an inner layer portion sandwiched between the first and second side portions and sandwiched between the first and second outer layer portions. Furthermore, in a cross-section traversing the center of the laminate in the length direction, the dielectric layer at the center of the thickness direction of the inner layer portion contains particles with holes as dielectric particles.
[0030] use Figures 1-3 One method for describing a multilayer ceramic capacitor is described. Figure 1 This is a three-dimensional view showing the shape of a multilayer ceramic capacitor. Figure 2 yes Figure 1 The cross-sectional view of the multilayer ceramic capacitor shown is taken along line II-II. Figure 3 yes Figure 1 The cross-sectional view of the multilayer ceramic capacitor shown is taken along line III-III.
[0031] The multilayer ceramic capacitor (100) comprises: a multilayer body (6) including multiple dielectric layers (2) and multiple internal electrode layers (4) stacked together; and a pair of external electrodes (8a, 8b) disposed on the two end faces (14a, 14b) of the multilayer body (6). The multilayer ceramic capacitor (100) and the multilayer body (6) have a generally rectangular parallelepiped shape. The term "generally rectangular parallelepiped" does not simply include a rectangular parallelepiped, but also includes a rectangular parallelepiped with rounded corners and / or edges. Here, a corner is the portion where three faces of the multilayer body (6) intersect, and an edge is the portion where two faces of the multilayer body intersect. Preferably, the multilayer ceramic capacitor (100) and the multilayer body (6) have a rectangular parallelepiped shape with rounded corners and / or edges.
[0032] The multilayer ceramic capacitor (100) and the multilayer (6) have a first main surface (10a) and a second main surface (10b) opposite each other in the thickness direction T, a first side surface (12a) and a second side surface (12b) opposite each other in the width direction W, and a first end surface (14a) and a second end surface (14b) opposite each other in the length direction L. Here, the thickness direction T refers to the direction in which the dielectric layer (2) and the internal electrode layer (4) are stacked. The length direction L refers to the direction orthogonal to the thickness direction T and opposite to the end surfaces (14a, 14b). The width direction W is the direction orthogonal to both the thickness direction T and the length direction L. The surface containing the thickness direction T and the width direction W is defined as the WT surface, the surface containing the width direction W and the length direction L is defined as the LW surface, and the surface containing the length direction L and the thickness direction T is defined as the LT surface.
[0033] The external electrodes (8a, 8b) include a first external electrode (8a) disposed on a first end face (14a) and a second external electrode (8b) disposed on a second end face (14b). Not only on the first end face (14a), the first external electrode (8a) may also wrap around a portion of the first main face (10a), the second main face (10b), the first side face (12a), and the second side face (12b). Furthermore, not only on the second end face (14b), the second external electrode (8b) may also wrap around a portion of the first main face (10a), the second main face (10b), the first side face (12a), and the second side face (12b). However, the first external electrode (8a) and the second external electrode (8b) are electrically separated and do not contact each other.
[0034] The internal electrode layer (4) comprises a plurality of first internal electrode layers (4a) and a plurality of second internal electrode layers (4b). Each of the first internal electrode layers (4a) and the second internal electrode layers (4b) consists of opposing electrode portions of approximately rectangular shape and lead-out electrode portions extending to end faces (14a, 14b) and connected to external electrodes (8a, 8b). That is, the plurality of first internal electrode layers (4a) extend to the first end face (14a) via the lead-out electrode portions, and are therefore electrically connected to the first external electrode (8a). In addition, the plurality of second internal electrode layers (4b) extend to the second end face (14b) via the lead-out electrode portions, and are therefore electrically connected to the second external electrode (8b). The first internal electrode layers (4a) and the second internal electrode layers (4b) are stacked alternately, such that a dielectric layer (2) is sandwiched between them in the thickness direction T. The first inner electrode layer (4a) and the second inner electrode layer (4b), which are sandwiched between the dielectric layer (2), are not electrically connected. Therefore, if a voltage is applied via the external electrodes (8a, 8b) and the lead-out electrode portions, charge accumulates between the opposing electrode portions of the first inner electrode layer (4a) and the opposing electrode portions of the second inner electrode layer (4b). The accumulated charge generates electrostatic capacitance, thereby demonstrating the function of a capacitor element.
[0035] The laminate (6) is composed of an inner layer (16), a first outer layer (18a), a second outer layer (18b), a first side layer (20a), and a second side layer (20b). The first side layer (20a) is a layered region extending along the first side surface (12a) and not containing the inner electrode layers (4a, 4b). Similarly, the second side layer (20b) is a layered region extending along the second side surface (12b) and not containing the inner electrode layers (4a, 4b). That is, the first side layer (20a) is a region sandwiched between the ends of the inner electrode layers (4a, 4b) on the first side surface (12a) and the first side surface (12a), and the second side layer is a region sandwiched between the ends of the inner electrode layers (4a, 4b) on the second side surface (12b) and the second side surface (12b).
[0036] The first outer layer (18a) is the region sandwiched between the first side (20a) and the second side (20b) and between the inner electrode layer (4a, 4b) closest to the first main surface (10a) and the first main surface (10a) among the plurality of inner electrode layers (4a, 4b). The second outer layer (18b) is the region sandwiched between the first side (20a) and the second side (20b) and between the inner electrode layer (4a, 4b) closest to the second main surface (10b) and the second main surface (10b) among the plurality of inner electrode layers (4a, 4b). The inner layer (16) is the region sandwiched between the first outer layer (18a) and the second outer layer (18b), that is, the region disposed between the inner electrode layer closest to the first main surface (10a) and the inner electrode layer closest to the second main surface (10b). This inner layer functions as a capacitor element. In summary, the inner layer (16) that performs the function of the capacitor element is sandwiched between the first outer layer (18a) and the second outer layer (18b) in the stacking (thickness) direction, and they are sandwiched together by the first side (20a) and the second side (20b) in the width direction.
[0037] The dimensions of the multilayer ceramic capacitor (100) and the laminate (6) are not particularly limited. For example, the length L dimension is 0.2 mm or more and 3.2 mm or less, the width W dimension is 0.1 mm or more and 2.5 mm or less, and the lamination T dimension is 0.1 mm or more and 2.5 mm or less. Furthermore, although in Figures 1-3 The diagram shows that the length dimension L is larger than the width dimension W, but the multilayer ceramic capacitor of this embodiment is not limited to multilayer ceramic capacitors having such dimensions. The length dimension L may also be smaller than the width dimension W.
[0038] <Inner Layer - Dielectric Layer>
[0039] The dielectric layer, together with the internal electrode layer, constitutes the inner layer of a multilayer ceramic capacitor. This dielectric layer contains dielectric particles (dielectric grains). These dielectric particles are composed of perovskite oxide and are the main component of the dielectric layer. The dielectric layer comprises a sintered polycrystalline (ceramic) structure with numerous dielectric particles bonded via grain boundaries and triple points. The dielectric layer can be described as a dielectric ceramic primarily composed of perovskite oxide. Furthermore, the term "main component" refers to the component with the highest proportion in the dielectric layer. The proportion of the dielectric particles (perovskite oxide) that are the main component in the dielectric layer can be 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or even 90% by mass or more.
[0040] Perovskite oxides have a composition that can be represented by the general formula ABO3, and at room temperature, they exhibit cubic, tetragonal, orthorhombic, and rhombohedral crystal structures similar to cubic crystals. Furthermore, atoms of the A-site element (hereinafter referred to as "A-site atoms") and atoms of the B-site element (hereinafter referred to as "B-site atoms") are ionized and occupy the A-site and B-site of the perovskite structure, respectively. Examples of A-site elements include elements with relatively large ion sizes such as barium (Ba), calcium (Ca), and strontium (Sr), while examples of B-site elements include elements with relatively small ion sizes such as titanium (Ti), zirconium (Zr), and hafnium (Hf). There are no particular limitations on the combination of A-site and B-site elements as long as the perovskite structure is maintained. Each A-site element and B-site element may consist of only one element, or multiple elements may be combined. Furthermore, as long as the perovskite structure is maintained, the molar ratio of A-site and B-site elements can deviate from 1:1.
[0041] Specific examples of perovskite oxides include barium titanate (BaTiO3) compounds, calcium titanate (CaTiO3) compounds, strontium titanate (SrTiO3) compounds, and their mixed crystals and solid solutions. Preferably, the A-site element comprises barium (Ba), and the B-site element comprises titanium (Ti). That is, preferably, the perovskite oxide is a barium titanate (BaTiO3) compound. BaTiO3 exhibits large spontaneous polarization at room temperature. Therefore, it is a strong dielectric exhibiting a high dielectric constant. By using BaTiO3 compounds as the main component, it is possible to achieve further increases in capacitance of the capacitor. In addition, BaTiO3 compounds not only contain BaTiO3, but also compounds in which a portion of the Ba in BaTiO3 is replaced by Sr and / or other A-site elements such as Ca, or compounds in which a portion of the Ti is replaced by Zr and / or other B-site elements such as Hf. However, the proportion of Ba in the A-site element is preferably 70% or more by molar ratio, more preferably 80% or more, and even more preferably 90% or more. Furthermore, the proportion of Ti in the B-site element is preferably 70% or more by molar ratio, more preferably 80% or more, and even more preferably 90% or more. Alternatively, the A-site element may not contain any components other than Ba and unavoidable impurity elements, and the B-site element may not contain any components other than Ti and unavoidable impurity elements. Here, unavoidable impurities refer to components that are unavoidably mixed in during the manufacturing process.
[0042] The dielectric layer may also contain secondary components. There are no limitations on what constitutes a secondary component; examples include rare earth elements (RE), magnesium (Mg), manganese (Mn), iron (Fe), chromium (Cr), and cobalt (C). o Rare earth elements (REs) include nickel (Ni), silicon (Si), aluminum (Al), vanadium (V), and their compounds. Rare earth elements (REs) are the collective term for elements that constitute the group consisting of scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71 in the periodic table. Rare earth elements (REs) are preferably selected from one or more elements selected from the group consisting of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and yttrium (Y). These elements may be included individually or in combination as sub-components.
[0043] When the dielectric layer contains secondary components, the form in which these components exist is not limited. The secondary components can be present in any of the dielectric particles, grain boundaries, and triple points. When contained within dielectric particles, they can also be contained in a solid solution state. In this case, they can occupy A-sites, B-sites, or both sites simultaneously in the perovskite oxide (ABO3). Furthermore, the distribution of secondary components within the dielectric particles can be uniform or non-uniform.
[0044] Dielectric particles can also include core-shell particles. Core-shell particles are particles with a structure where at least a portion of the byproducts are dissolved in a high concentration on the surface (shell) of the particle, and the byproducts are dissolved in a low concentration or not dissolved at all in the central part (core). By giving dielectric particles a core-shell structure, the temperature characteristics of the dielectric constant can be flattened, thus improving reliability. Specifically, the concentrations of byproducts in the core and shell of core-shell particles are different, resulting in different temperature characteristics of the dielectric constant. Therefore, the temperature characteristics of the dielectric constant throughout the particle can be flattened. Furthermore, by dissolving byproducts such as rare-earth elements, which function as donors and acceptors, in the shell, the movement of oxygen holes that cause insulation degradation can be suppressed, significantly improving the reliability of multilayer ceramic capacitors.
[0045] Furthermore, the presence of a core-shell structure can be determined by comparing the concentration of each secondary component in the particle's center (core) with the concentration in the portion of the particle that enters the particle at a distance of approximately 10 nm from the interface between the particle and the grain boundary phase (shell). If the concentration of the secondary component in the shell is 150% or more greater than that in the core, the particle can be identified as a core-shell particle.
[0046] Dielectric particles can also contain homogeneously dissolved particles. Homogeneously dissolved particles are particles with either homogeneous secondary components or undissolved secondary components uniformly dissolved within them. Homogeneously dissolved particles are also called non-core-shell particles. To achieve homogeneous dissolution, it is best to introduce the secondary components into the particles along with grain growth, and for this purpose, it is best to grow the particles to a certain size. By using particles in this way, where secondary components are uniformly dissolved, the dielectric constant can be further improved. Core-shell particles have the advantage of flattening the temperature characteristics of the dielectric constant and improving reliability, but they have limitations in improving the dielectric constant itself. In contrast, by using homogeneously dissolved particles, the dielectric constant can be significantly improved.
[0047] In the multilayer ceramic capacitor of this embodiment, in a cross-section traversing the central portion of the multilayer in the longitudinal direction, the dielectric layer at the central portion of the inner layer in the thickness direction contains particles with vacancies (vacancies-bearing particles) as dielectric particles (dielectric particles). That is, when the multilayer ceramic capacitor is processed to expose a surface (WT surface) traversing the central portion of the multilayer in the longitudinal direction and including both the width and thickness directions, some or all of the dielectric particles in the dielectric layer at a given position on this WT surface are vacancies-bearing particles. In these vacancies-bearing particles, vacancies exist within the particles.
[0048] By incorporating vacant particles, various properties of the dielectric layer can be improved, such as dielectric constant, temperature characteristics of dielectric constant, and reliability. That is, dielectric particles without vacant particles sometimes have low crystallinity. If the particle crystallinity is low, during the firing process in manufacturing multilayer ceramic capacitors, byproduct elements may excessively diffuse into the particle interior, degrading various properties. For example, when aiming to form core-shell particles, byproduct elements may sometimes diffuse through the shell to the core, thus disrupting the core-shell structure. Furthermore, when aiming to form uniform solid solution particles, byproduct elements may sometimes excessively dissolve within the particles, making it difficult to obtain the desired properties. In contrast, vacant particles have high crystallinity around the vacant holes, thus suppressing excessive diffusion of byproduct elements. For example, when the dielectric particles are core-shell particles, even if grain growth occurs during the firing process, the diffusion and solid solution of byproducts will not exceed what is necessary. Because it allows grain growth without disrupting the core-shell structure, it is possible to achieve a balance between high dielectric constant, flat temperature characteristics, and excellent reliability.
[0049] There is no particular limitation on the number of holes in a particle with holes. A particle may contain one hole or multiple holes. Furthermore, there is no particular limitation on the distribution of holes within the particle. Typically, holes exist near the center of the particle.
[0050] The presence and proportion of vacancy-bearing particles can be investigated as follows: First, the multilayer ceramic capacitor is processed by methods such as grinding, milling, and / or cutting to expose its cross-section. This cross-section is a plane that runs through the center of the multilayer ceramic capacitor in the length (L) direction and includes the width (W) and thickness (T) directions, i.e., the WT plane. Next, the obtained cross-section is observed using a transmission electron microscope (TEM) to obtain a high-angle scattered annular dark field (HAADF) image, and the presence and proportion of vacancy-bearing particles are investigated based on this image. Holes appear as black dots among the particles and can therefore be easily found. The approximate center of the thickness (T) direction in the WT plane is observed. If a dielectric layer exists in the center of the thickness direction, only that dielectric layer needs to be observed. On the other hand, if an internal electrode layer exists in the center of the thickness direction, only the dielectric layer adjacent to that internal electrode layer needs to be observed. More than 100 dielectric particles are observed. For example, observe with a field of view of 1000nm × 1000nm, and count the number of holes among the dielectric particles present in this field of view. If there are no more than 100 dielectric particles in this field of view, it is sufficient to include multiple adjacent fields of view for investigation. For example, it is sufficient to connect multiple fields of view and observe in a total field of view area of 3μm × 3μm. Then, simply count the number of dielectric particles (N) and the number of holes (n), and calculate the ratio of the number of holes (n / N).
[0051] Preferably, vacancy-bearing particles are present near the center of the inner layer in the width direction. That is, in a cross-section traversing the center of the laminate in the length direction, the dielectric layer at the center of the thickness direction of the inner layer intermediate region preferably contains vacancy-bearing particles as the dielectric particles. The so-called inner layer intermediate region is the region of the inner layer located in the middle of the width direction. Specifically, when the laminate is divided into a first inner layer side region, a second inner layer side region, and an inner layer intermediate region, the region sandwiched between the first inner layer side region and the second inner layer side region is the inner layer intermediate region. Furthermore, the first inner layer side region is the region within the inner layer that occupies the portion below the end distance from the interface between the inner layer and the first side. Here, the so-called end distance is any smaller distance between W / 10 and 40 μm when the width of the laminate is set to W. The first inner layer side region can also be described as the region within the inner layer that is sandwiched between the interface between the inner layer and the first side and a surface separated from the interface by the end distance. Furthermore, the second inner layer side region is the region within the inner layer that occupies the portion below the end distance from the interface between the inner layer and the second side. The second inner layer side region can also be described as the region within the inner layer that is sandwiched between the interface between the inner layer and the second side and a surface separated from that interface by the end distance.
[0052] Preferably, the number of vacant particles is higher near the center of the width direction of the inner layer. Specifically, in a cross-section traversing the center of the length direction of the laminate, the ratio (Cn / CN) of the number of vacant particles among the dielectric particles in the center of the thickness direction of the inner layer's intermediate region is preferably 15% or more. By increasing the proportion of vacant particles in the intermediate region of the inner layer, further improvements can be achieved in the dielectric constant, temperature characteristics of the dielectric constant, and reliability of the dielectric layer. The ratio (Cn / CN) can be 20% or more, 25% or more, 30% or more, 35% or more, or 40% or more. There is no particular upper limit to the ratio (Cn / CN). It can also be less than 100%, less than 80%, or less than 60%.
[0053] Preferably, vacuolated particles are present near the ends of the inner layer in the width direction. That is, in a cross-section traversing the central portion in the length direction of the laminate, the dielectric layer at the central portion in the thickness direction of at least one of the first inner layer side regions and the second inner layer side regions preferably contains vacuolated particles as dielectric particles. This allows for further improvement in reliability. When a multilayer ceramic capacitor operates, the electric field concentrates near the ends of the inner electrode layers, making insulation breakdown prone to occur near the ends. By providing highly crystalline vacuolated particles in the dielectric layer near the ends, the progression of insulation breakdown can be suppressed, resulting in a significant improvement in reliability.
[0054] Preferably, the number of vacant particles is higher near the ends of the inner layer in the width direction. That is, in a cross-section traversing the central portion in the length direction of the laminate, the proportion (Wn / WN) of vacant particles among the dielectric particles at the central thickness direction of at least one of the first inner layer side regions and the second inner layer side regions is preferably greater than the proportion (Cn / CN) of vacant particles among the dielectric particles at the central thickness direction of the inner layer middle region. Furthermore, in a cross-section traversing the central portion in the length direction of the laminate, the proportion (Wn / WN) of vacant particles among the dielectric particles at the central thickness direction of at least one of the first inner layer side regions and the second inner layer side regions is preferably 25% or more. By increasing the proportion of vacant particles in the dielectric layer near the ends in this way, reliability can be significantly improved. The proportion (Wn / WN) can be 30% or more, 35% or more, or 40% or more. There is no particular upper limit to the proportion (Wn / WN). It can also be below 100%, below 80%, or below 60%.
[0055] The average aperture of the holes is preferably 1 nm or more and 50 nm or less, particularly preferably 10 nm or more and 30 nm or less. By limiting the aperture to a given value or more, the effect of improving the crystallinity of the particles can be fully realized, and the capacitance temperature characteristics can be significantly suppressed. Furthermore, by limiting the aperture to a given value or less, the degradation of hole-based dielectric properties can be suppressed, and the dielectric constant can be significantly improved.
[0056] The average particle size of the dielectric particles is preferably 100 nm or more and 500 nm or less, particularly preferably 130 nm or more and 300 nm or less. By limiting the average particle size to a given value or more, the effect of improving the crystallinity of the particles can be fully utilized, and the capacitance temperature characteristics can be significantly suppressed. Furthermore, by limiting the average particle size to a given value or less, the dielectric layer can be made thinner, which helps to increase the capacitance of the multilayer ceramic capacitor and improves reliability. In addition, the above-mentioned average particle size refers to the average particle size of the dielectric particles as a whole, including not only particles with holes but also particles without holes.
[0057] The thickness of the dielectric layer is preferably 0.30 μm or more and 1.00 μm or less, more preferably 0.40 μm or more and 0.50 μm or less, and even more preferably 0.40 μm or more and 0.45 μm or less. By setting the thickness of the dielectric layer to a given value or more, insulation breakdown and lifespan degradation can be suppressed when using multilayer ceramic capacitors. Furthermore, by setting the thickness of the dielectric layer to a given value or less, the dielectric layer can be made thinner, enabling further increases in capacitance of multilayer ceramic capacitors. The number of dielectric layers is not particularly limited. Preferably, the number of dielectric layers constituting the outer and inner layers is 100 or more and 2000 or less.
[0058] The composition of the dielectric layer occupying the inner layer is not particularly limited. However, the preferred composition includes barium titanate (BaTiO3) as the main component, and further, relative to 100 mol parts of titanium (Ti), as a secondary component, dysprosium (Dy) is included in an amount of 0.6 to 2.0 mol, manganese (Mn) in an amount of 0.08 to 0.4 mol, magnesium (Mg) in an amount of 0.01 to 0.2 mol, silicon (Si) in an amount of 0.6 to 2.0 mol, nickel (Ni) in an amount of 0.2 to 5.0 mol, aluminum (Al) in an amount of 0.04 to 0.3 mol, and vanadium (V) in an amount of 0.04 to 0.2 mol.
[0059] <Inner Layer - Internal Electrode Layer>
[0060] The inner electrode layers (first inner electrode layer and second inner electrode layer) together with the dielectric layer constitute the inner layer. Furthermore, the inner electrode layers are composed of a counter electrode portion and a lead-out electrode portion. The counter electrode portion holds the dielectric layer and functions as a capacitor element. The lead-out electrode portion electrically connects the counter electrode portion and the external electrode. The inner electrode layers contain a conductive metal. As the conductive metal, any known electrode material such as nickel (Ni), copper (Cu), silver (Ag), palladium (Pd), silver (Ag)-palladium (Pd) alloys, and / or gold (Au) can be used. However, from the viewpoint of cost reduction, Ni and Cu, as base metals, are preferred, and Ni is particularly preferred.
[0061] The internal electrode layer may also contain components other than conductive metals. Ceramic components, which function as common materials, can be listed as examples. By adding common materials, the shrinkage behavior of the internal electrode layer can be matched with that of the dielectric layer during the firing process in the manufacture of the multilayer ceramic capacitor. Therefore, defects such as peeling of the internal electrode layer caused by differences in shrinkage behavior can be suppressed. As a ceramic component, dielectric particles such as BaTiO3-based compounds contained in the dielectric layer are preferred. Furthermore, the thickness of the internal electrode layer is preferably 0.30 μm or more and 0.40 μm or less, more preferably 0.30 μm or more and 0.35 μm or less. By setting the internal electrode thickness to a given value or more, problems such as electrode breakage can be prevented. Furthermore, by setting it to a value or less, the proportion of the dielectric layer in the capacitor can be prevented from decreasing, which contributes to larger capacitance. Moreover, the number of internal electrode layers is preferably 10 or more and 1000 or less.
[0062] Tin (Sn) may also be present at the interface between the dielectric layer and the inner electrode layer. In the presence of Sn, it can exist in a layered form parallel to the inner electrode layer, or it can be dispersed. Furthermore, Sn can be dissolved within the inner electrode layer, or it can be dissolved within the dielectric particles constituting the dielectric layer.
[0063] <Outer layer>
[0064] The outer layers (first outer layer and second outer layer) are respectively disposed above and below the inner layers. The outer layers are regions made of dielectric ceramic and do not contain an internal electrode layer. The composition of the outer layers may be the same as or different from the dielectric layer contained in the inner layers. If the composition of the outer layers is the same as the inner layers, the dielectric green sheet used to form the inner layers can also be used to form the outer layers during the manufacture of the multilayer ceramic capacitor.
[0065] <Side view>
[0066] Side portions (first side portion, second side portion) are configured along the side surface of the multilayer ceramic capacitor to clamp the inner and outer layers. The inner layer side portions are also called lateral spacers. The side portions (lateral spacers) are regions made of dielectric ceramic and do not contain internal electrode layers. By providing the side portions, it is possible to prevent moisture from penetrating into the inner layers from the sides.
[0067] The side portion can also be integrally formed together with the inner and outer layers during the manufacturing of a multilayer ceramic capacitor. In this case, the composition and microstructure of the dielectric layer constituting the side portion are continuous with the dielectric layers constituting the inner and / or outer layers. Alternatively, the side portion can be formed independently of the inner and outer layers. Specifically, this can be achieved by adhering an unprocessed side portion body to the side of the multilayer sheet that forms the inner and outer layers, and then firing the unprocessed body. In this case, the composition and / or microstructure of the dielectric layer constituting the side portion are discontinuous with the dielectric layers constituting the inner and / or outer layers. Therefore, a physical / chemical boundary exists between the side portion and the inner and / or outer layers.
[0068] Preferably, the first and second sides contain dielectric particles containing barium (Ba) and titanium (Ti), and further, relative to 100 molar parts of titanium (Ti), contain at least one of magnesium (Mg) of 1.00 mol parts and 3.00 mol parts and manganese (Mn) of 0.50 mol parts and 2.00 mol parts, with the total content of magnesium (Mg) and manganese (Mn) being 5.00 mol parts or less. By setting the amount of Mg to 1.00 mol parts or more, or the amount of Mn to 0.50 mol parts or more, the moisture load resistance characteristics can be improved. In addition, by setting the amount of Mg to 3.00 mol parts or less and the amount of Mn to 2.00 mol parts or less, the capacitance drop can be suppressed.
[0069] <External Electrode>
[0070] The external electrodes (first external electrode and second external electrode) function as input and output terminals of the multilayer ceramic capacitor. Known structures can be used as the external electrodes. For example, a base electrode layer and a plating layer disposed on the base electrode layer may be included. The base electrode layer includes at least one layer selected from sintered layers, resin layers, and thin film layers. The sintered layer is formed by sintering after applying a conductive paste containing glass and metal to the multilayer. Sintering can be performed simultaneously with the firing of the multilayer, or it can be performed after the multilayer has been fired. The sintered layer can be a single layer or composed of multiple layers. The metal included in the sintered layer is preferably copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), a silver (Ag)-palladium (Pd) alloy, and / or gold (Au). The resin layer includes conductive particles and a thermosetting resin. The resin layer can be a single layer or composed of multiple layers. The thin film layer can be formed by thin film formation methods such as sputtering and vapor deposition, and is a layer with a thickness of less than 1 μm on which metal particles are deposited. The plating layer contains metals such as copper (Cu), nickel (Ni), tin (Sn), silver (Ag), palladium (Pd), silver (Ag)-palladium (Pd), and / or gold (Au). The plating layer can be a single layer or composed of multiple layers. Preferably, the plating layer has a two-layer structure of Ni plating and Sn plating. The Ni plating layer can prevent the solder from eroding the substrate layer when mounting the multilayer ceramic capacitor. In addition, the Sn plating layer can improve the wettability of the solder, thus making the mounting of the multilayer ceramic capacitor easier.
[0071] Alternatively, an external electrode layer can be formed by plating without a base electrode layer. In this case, the plating layer is directly disposed on the laminate and directly connected to the lead-out electrode portion of the internal electrode layer. However, a catalyst can also be disposed on the laminate as a pretreatment. Preferably, the plating layer comprises a first plating layer and a second plating layer disposed on the first plating layer. Furthermore, other plating layers may be disposed on the second plating layer. The first and second plating layers, for example, comprise a metal selected from the group consisting of copper (Cu), nickel (Ni), tin (Sn), lead (Pd), gold (Au), silver (Ag), palladium (Pd), bismuth (Bi), and zinc (Zn), or an alloy comprising such metal. When the internal electrode layer comprises Ni, the first plating layer preferably comprises Cu, which has good bonding properties with Ni. Furthermore, the first plating layer preferably also comprises Ni, which has good solder resist properties. The second plating layer preferably comprises Sn or Au, which have good solder wettability.
[0072] However, the plating layer is not limited to consisting of a first plating layer and a second plating layer. It is also possible to omit the second plating layer and consist only of the first plating layer. Other plating layers may also be provided on the second plating layer. In either case, it is preferable that the plating layer does not contain glass. Furthermore, the metal content of the plating layer is preferably 99% by volume or more. The plating layer undergoes grain growth along its thickness direction and is columnar.
[0073] (2) Manufacturing method of multilayer ceramic capacitors
[0074] The manufacturing method of the multilayer ceramic capacitor of this embodiment is not limited as long as the above-mentioned necessary conditions are met. However, it is preferred to manufacture it by the following method. The preferred manufacturing method includes the following steps: a step of synthesizing the main component raw material for the dielectric layer (synthesis step); a step of mixing the secondary component raw material with the main component raw material to obtain the dielectric raw material (mixing step); a step of adding and mixing the binder and solvent into the dielectric raw material to form a slurry, and forming the resulting slurry into a dielectric green sheet (forming step); a step of printing a patterned conductive paste layer on the surface of the dielectric green sheet using conductive paste for internal electrodes (printing step); a step of stacking and pressing multiple dielectric green sheets to form a laminate (lamination step); a step of cutting the obtained laminate into laminated pieces (cutting step); a step of attaching unprocessed side parts to the sides of the obtained laminated pieces to form an unprocessed body part (side part forming step); a step of performing a debinding treatment and a firing treatment on the obtained unprocessed body part to form a body part (firing step); and a step of forming an external electrode on the obtained body part to form a laminated ceramic capacitor (external electrode forming step). Details of each step are described below.
[0075] <Synthesis Process>
[0076] In the synthesis process, the main component raw materials used to form the dielectric layer are synthesized. As the main component raw materials, oxide powders with a perovskite structure, such as BaTiO3-based compounds, are used. Preferably, the main component raw materials are synthesized using liquid-phase methods such as the sol-gel method, alkoxide method, solvothermal method, and hydrothermal synthesis method. In the sol-gel method, sols or gels of inorganic or organic salts of Ba and Ti are used as raw materials, mixed, and calcined to produce oxide powders. In the alkoxide method, alkoxides of Ba and Ti are used as raw materials, mixed, and calcined to produce oxide powders. In the solvothermal method, inorganic or organic compounds of Ba and Ti are placed together with a solvent in a sealed container, and high temperature and pressure are applied to synthesize the oxide powders. The hydrothermal method is a type of solvothermal method that uses water as a solvent.
[0077] <Mixed Processes>
[0078] In the mixing process, secondary components (Ni, Re, Mg, Mn, Si, Al, V, etc.) are mixed with the main component raw material to form the dielectric raw material. As secondary component raw materials, any known ceramic raw materials such as oxides, carbonates, hydroxides, nitrates, organic acid salts, alkoxides, and / or chelates can be used. The mixing method is not particularly limited. For example, a method can be listed as follows: using a ball mill to wet mix and pulverize the weighed main component raw material and secondary component raw material together with pulverizing media and pure water. In the case of wet mixing, it is sufficient to dry the mixture.
[0079] <Molding Process>
[0080] In the molding process, binders and solvents are added to the dielectric raw material and mixed to form a slurry, which is then molded into a green dielectric sheet. After firing, the green dielectric sheet becomes the dielectric layer constituting the inner and outer layers of a multilayer ceramic capacitor. As the binder, any known organic binder such as polyvinyl butyral binder can be used. Furthermore, as the solvent, any known organic solvent such as toluene or ethanol can be used. Additives such as plasticizers may be added as needed. Molding can be performed using any known method such as the rip-in method. The thickness of the molded sheet is, for example, less than 1 μm.
[0081] <Printing Process>
[0082] In the printing process, a patterned conductive paste layer is formed on the surface of a dielectric green sheet using conductive paste. After firing, the conductive paste layer becomes the internal electrode layer. As the conductive metal contained in the conductive paste, conductive materials such as nickel (Ni), copper (Cu), silver (Ag), palladium (Pd), and alloys containing them can be used. However, nickel (Ni) is preferred. Furthermore, ceramic components that function as common materials can also be added to the conductive paste. The main component raw material of the dielectric layer can be used as the ceramic component. The method for forming the conductive paste layer is not particularly limited. For example, screen printing, gravure printing, and other methods can be listed.
[0083] <Layering Process>
[0084] In the lamination process, multiple dielectric green sheets are stacked and pressed together to create a laminated block. At this stage, multiple dielectric green sheets with conductive paste layers are stacked, with dielectric green sheets without conductive paste layers sandwiched between them from above and below. The green sheets without conductive paste layers become the outer layer of the laminated ceramic capacitor after a firing process. Conversely, the green sheets with conductive paste layers become the dielectric layer constituting the inner layer of the laminated ceramic capacitor. The number of green sheets stacked can be adjusted to obtain the desired capacitance.
[0085] <Cutting process>
[0086] In the cutting process, the resulting laminated block is cut into laminated pieces. Cutting is performed such that pieces of a given size are obtained, and at least a portion of the conductive paste layer is exposed on the end face of the laminated piece.
[0087] <Side Forming Process>
[0088] A side-forming process is provided as needed. In this process, the side portion is formed independently of the inner and outer layers. During the side-forming process, the unprocessed side portion is attached to the side of the laminated sheet, becoming the unprocessed body portion. The conductive paste layer exposed on the side of the laminated sheet is covered by the unprocessed side portion. Furthermore, the unprocessed side portion becomes the side of the laminated ceramic capacitor after firing. As raw materials for the unprocessed side portion, main component raw materials and auxiliary component raw materials used to make the dielectric layer can be used. However, it is not necessary for the composition of the side portion to be the same as the composition of the dielectric layer; a different composition can be used. For example, only a portion of the auxiliary components of the dielectric layer can be used, or auxiliary components different from those of the dielectric layer can be added. On the other hand, the composition of the side portion can also be the same as that of the dielectric layer.
[0089] The side-part unprocessed body can be fabricated and attached using known methods. For example, a method can be used to prepare a green sheet from side-part raw material powder and then bond the green sheet to the side of a laminated sheet. In this case, to ensure reliable bonding of the green sheet, an adhesive aid such as an organic solvent can be pre-applied to the side of the laminated sheet. Alternatively, a method can be used to prepare a paste from side-part raw material powder, apply the paste to the side of the laminated sheet, and allow it to dry. Furthermore, the side-part unprocessed body can be a single layer or a laminate containing multiple layers. A side-part unprocessed body containing a laminate can be obtained by laminating multiple green sheets on the side of the laminated sheet and repeatedly applying and drying the paste. In addition, when the side part is integrally formed together with the inner layer and the outer layer, a portion of the dielectric green sheet laminated in the lamination process becomes the side part, so in this case, a separate side part forming process is not required.
[0090] Furthermore, as needed, the stacked pieces or unprocessed body parts are subjected to tumbling grinding. This process allows the corners and / or edges of the stacked pieces or unprocessed body parts to have rounded corners.
[0091] <Firing Process>
[0092] In the firing process, the laminated sheets or unprocessed body portion undergoes a debinding treatment and firing to form the body portion. Through the firing process, the conductive paste layer and the dielectric green sheet are co-fired, thus becoming the internal electrode layer and dielectric layer, respectively. The conditions for the debinding treatment are determined solely by the type of organic binder contained in the green sheet and the conductive paste layer. Furthermore, the firing process can be carried out at a temperature that sufficiently densifies the laminated sheets. For example, it can be carried out under the following conditions: a temperature of 1200°C or higher and 1300°C held for 0 minutes or more and 10 minutes or less. Furthermore, the firing is carried out in an atmosphere in which the BaTiO3-based compounds, as the main component, are not reduced, and the oxidation of the conductive material is suppressed. For example, an atmosphere with an oxygen partial pressure of 1.8 × 10⁻⁶. -9 ~8.7×10 -10 The firing process can be carried out using a N2-H2-H2O gas flow at MPa. Alternatively, annealing can be performed after firing.
[0093] <External Electrode Formation Process>
[0094] In the external electrode formation process, external electrodes are formed on the body portion to create a multilayer ceramic capacitor. The formation of the external electrodes can be performed using known methods. For example, a conductive paste, primarily composed of conductive materials such as Cu or Ni, is applied and fired onto the exposed end faces of the internal electrodes in the body portion to form a base layer. The base layer can also be formed by applying conductive paste to both end faces of the unprocessed body portion before firing, followed by a firing process. Electroplating is then performed after the base layer is formed to create a Ni, Sn, or similar plating film on the surface of the base layer. This process manufactures a multilayer ceramic capacitor.
[0095] Example
[0096] The following examples will illustrate this embodiment in more detail. However, the present invention is not limited to the following embodiments.
[0097] (1) Fabrication of multilayer ceramic capacitors
[0098] [Comparative Examples 1 to 3 and Examples 1 to 20]
[0099] Comparative Examples 1 to 3 and Examples 1 to 20 were used to manufacture multilayer ceramic capacitors by changing the manufacturing conditions and the composition of the dielectric layer, and the capacitors were evaluated.
[0100] Synthesis of Barium Titanate Powder
[0101] Barium titanate powder was prepared using a so-called hydrothermal synthesis method. First, titanium oxide (TiO2) powder and barium hydroxide (Ba(OH)2) powder were weighed, and pure water was added to prepare a slurry. Then, the slurry was placed in a sealed container, and the temperature was raised to 200–250°C while stirring. The liquid-phase reaction was then initiated by maintaining the temperature at 200–250°C for 4–24 hours. Next, the pressure inside the sealed container was restored to atmospheric pressure, heating was stopped, and the slurry was left to cool. After cooling, the slurry was removed from the sealed container and placed in a dryer to evaporate the moisture. The resulting barium titanate powder was used as the main component raw material.
[0102] The secondary components (Ni, Re, Mg, Mn, Si, Al, V) were weighed independently of the main component raw materials. Nickel oxide (NiO), rare earth oxides (Dy2O3, etc.), magnesium carbonate (MgCO3), manganese carbonate (MnCO3), silicon oxide (SiO2), aluminum oxide (Al2O3), and vanadium oxide (V2O5) were used as secondary component raw materials.
[0103] Next, secondary raw materials are added to the main raw material and wet-mixed using a ball mill, followed by drying and heat treatment to obtain the dielectric raw material. A polyvinyl butyral binder and ethanol as an organic solvent are added to the obtained dielectric raw material and wet-mixed for a given time using a ball mill to prepare a slurry. This slurry is then sheet-formed to produce a dielectric green sheet.
[0104] Next, a Ni-based conductive paste was screen-printed onto the surface of the obtained dielectric green sheet, and a pattern was formed for the conductive paste layer, which would become the internal electrode layer. Then, multiple green sheets with conductive paste layers were stacked, with green sheets without conductive paste layers placed above and below them, and the entire assembly was pressed together to create a stacked block. The resulting stacked block was then cut into smaller stacked pieces using a dicing machine. The stacking process was performed so that the ends with exposed conductive paste layers alternated. Furthermore, the cutting process exposed the conductive paste layer on the sides.
[0105] Side green sheets (unprocessed side parts) are attached to the two sides of the cut, stacked pieces that expose the conductive paste layer to form the unprocessed main body. Except for changing the proportions of the main component raw materials and the auxiliary component raw materials, the side green sheets are manufactured in the same way as the dielectric green sheets.
[0106] The obtained green body portion was subjected to heat treatment in an N2 gas stream at a maximum temperature of 270°C, and further subjected to heat treatment in an N2-H2O-H2 gas stream at a maximum temperature of 800°C. Then, firing was performed in an N2-H2O-H2 gas stream. In the comparative example, firing was performed under conditions of a maximum temperature of 1050 to 1090°C, a temperature increase rate of 50°C / min, a holding time of 60 minutes, and an oxygen partial pressure of 7.8×10 -11 to 3.3×10 -9 MPa. In addition, in the example, firing was performed under conditions of a maximum temperature of 1230 to 1400°C, a temperature increase rate of 20 to 60°C / s, a holding time set to be shorter than that in the comparative example, and an oxygen partial pressure of 5.0×10 -13 to 1.7×10 -12 MPa. Next, heat treatment was performed for 60 minutes in an N2-H2O-H2 gas stream at a maximum temperature of 1050°C. Thus, a stacked body of the multilayer ceramic capacitor was obtained.
[0107] A conductive paste containing copper (Cu) as a main component was applied to the end face of the fired stacked body from which the internal electrode layers were led out. Then, the applied conductive paste was baked at 900°C to form a base layer of an external electrode. Further, Ni plating and Sn plating were sequentially performed on the surface layer of the base layer by wet plating. A multilayer ceramic capacitor was produced in this manner.
[0108] Regarding the produced multilayer ceramic capacitor, the length L dimension was 1.0 mm, the width direction W dimension was 0.5 mm, and the thickness direction T dimension was 0.5 mm. Further, the thickness of the dielectric layer in the inner layer portion was 0.48 μm, the thickness of the internal electrode layer was 0.38 μm, and the number of dielectric layers was 50.
[0109] (2) Evaluation
[0110] Various characteristics of the produced multilayer ceramic capacitor were evaluated as follows.
[0111] <SEM Observation>
[0112] Using a scanning electron microscope (SEM), the WT plane of the multilayer ceramic capacitor was observed, and the thickness of the dielectric layer and the diameter of dielectric particles were investigated. Specifically, the multilayer ceramic capacitor was polished to the center in the length (L) direction to expose the cross section (WT plane). Next, on a total of 5 lines: the center line in the width direction W, and two lines drawn at equal intervals on both sides from the center line toward the width direction W, the thickness of the dielectric layer in the inner layer portion near the center in the thickness direction was measured, and the average value thereof was taken as the thickness of the dielectric layer.
[0113] Furthermore, an SEM image of the dielectric particles in the dielectric layer in the exposed cross section was captured under the conditions of a magnification of 5000 times, an acceleration voltage of 15 kV, and a field of view of 30 μm × 30 μm. Next, image processing software was used to identify the edges of all the dielectric particles and calculate the cross-sectional area of the particles, and the equivalent circular diameter was calculated as the particle diameter based on this area. The diameters of all the dielectric particles included in the captured range were measured, excluding the dielectric particles that were partially missing and thus not fully captured, and the average value thereof was obtained.
[0114] <TEM Observation>
[0115] The WT surface of the multilayer ceramic capacitor was observed using a transmission electron microscope (TEM), and the presence or absence and the proportion of particles with voids were investigated. Specifically, the multilayer ceramic capacitor was ground to the center in the length (L) direction to expose the WT surface, and further processed to select a thin section specimen including the WT surface. Then, the thin section specimen was observed using TEM, and a high-angle annular dark field (HAADF) image was obtained. During observation, the cross section (WT surface) of the multilayer ceramic capacitor was divided into a side portion, an outer layer portion, and an inner layer portion, and the inner layer portion was further divided into an inner layer middle region and an inner layer side region. Then, observation was performed at the center of each of the inner layer middle region and the inner layer side region with a field of view of 1000 nm × 1000 nm. More than 100 dielectric particles were observed. When more than 100 dielectric particles were not included in one field of view, observation was performed by connecting a plurality of fields of view.
[0116] Then, the number of dielectric particles (CN, WN) and the number of particles with voids among the dielectric particles (Cn, Wn) were counted for the inner layer middle region and the inner layer side region, respectively, and the proportion of the number of particles with voids (Cn / CN, Wn / WN) was calculated. In addition, the pore diameters of a plurality of particles with voids were measured, and the average value thereof was calculated.
[0117] <Relative Permittivity>
[0118] The electrostatic capacitance of the dielectric layer was measured using an automatic bridge measuring instrument. 100 samples were measured under the conditions of a temperature of 25°C, an effective voltage of 0.5 Vrms, and a frequency of 1 kHz. Based on the obtained electrostatic capacitance, the relative permittivity (ε was calculated using the thickness of the dielectric layer and the counter electrode area r ), and the average value thereof was obtained. Then, based on the obtained value of the relative permittivity, the samples were graded according to the following criteria.
[0119] A: The relative permittivity is 3000 or more and 4800 or less
[0120] B: Relative permittivity is 2500 or higher but less than 3000, or 4800 or higher but less than 5000.
[0121] C: Relative permittivity less than 2500 or more than 5000
[0122] <Temperature coefficient of capacitance>
[0123] The electrostatic capacitance of five samples was measured within a temperature range of -55℃ to 105℃ under conditions of an effective voltage of 1Vrms and a frequency of 1kHz. The temperature coefficient (rate of change) of the electrostatic capacitance was calculated based on the value at 25℃. Then, based on the obtained temperature coefficient values, the samples were graded according to the following criteria.
[0124] A: The absolute value of the rate of change at 85℃ is less than 10%.
[0125] B: The absolute value of the rate of change at 85℃ exceeds 10% but is less than 15%.
[0126] C: The absolute value of the rate of change at 85℃ exceeds 15%.
[0127] <Reliability>
[0128] Twenty samples underwent a high-temperature load test (HALT) at 150°C and 5V. The time until the insulation resistance reached 10000Ω was then determined as the failure time, and the mean time to failure (MTTF) was calculated based on the failure time using Weibull analysis. The samples were then graded according to the following criteria based on the obtained MTTF values.
[0129] A: MTTF is over 80 hours.
[0130] B: MTTF is 60 hours or more but less than 80 hours
[0131] C: MTTF less than 60 hours
[0132] (3) Evaluation Results
[0133] exist Figure 4 The image shows a cross-sectional TEM-HAADF image of the sample from Example 9. Voids are present in the areas indicated by arrows (black dots). Voids were confirmed to exist within several dielectric particles.
[0134] Table 1 summarizes the evaluation results of the multilayer ceramic capacitors obtained in Comparative Examples 1 to 3 and Examples 1 to 20. As shown in Table 1, in the samples of Examples 1 to 20, where the dielectric layer of the inner layer contains particles with holes, the relative permittivity (ε) is... rThe relative permittivity, capacitance temperature characteristics, and reliability (high-temperature load life) are all excellent. Furthermore, the higher the proportion of holes in the particles, the more significant the effect. In particular, the samples of Examples 8-12 and Examples 17-20, where the proportion of holes in the inner middle region is limited to 15% or more, the proportion of holes in the inner side region is limited to 25% or more, the average pore size of the holes is limited to 10 nm or more and 30 nm or less, and the average particle size of the holes is limited to 130 nm or more and 300 nm or less, exhibit superior relative permittivity, capacitance temperature characteristics, and reliability. In contrast, the samples of Comparative Examples 1-3, which do not contain holes, show a deterioration in any of these aspects.
[0135] [Table 1]
[0136] Table 1 Characteristics of Multilayer Ceramic Capacitors
[0137]
Claims
1. A multilayer ceramic capacitor comprising: a laminate having a first main surface and a second main surface opposite each other in the thickness direction, a first side surface and a second side surface opposite each other in the width direction, and a first end surface and a second end surface opposite each other in the length direction, and including a plurality of dielectric layers and a plurality of internal electrode layers stacked in the thickness direction; and a pair of external electrodes respectively disposed on the first end surface and the second end surface and connected to the plurality of internal electrode layers, wherein... The dielectric layer contains dielectric particles. The laminate is divided into: A layered first side portion, extending along the first side surface, does not include an internal electrode layer; The layered second side extends along the second side and does not include the internal electrode layer; The first outer layer is sandwiched between the first side and the second side, and is also sandwiched between the inner electrode layer closest to the first main surface and the first main surface; The second outer layer is sandwiched between the first side and the second side, and is also sandwiched between the inner electrode layer closest to the second main surface and the second main surface; as well as The inner layer is sandwiched between the first side and the second side, and is also sandwiched between the first outer layer and the second outer layer. In a cross-section traversing the center of the length direction of the laminate, the dielectric layer at the center of the thickness direction of the inner layer contains particles with holes as dielectric particles. When the width of the laminate is set to W, the inner layer is divided into: The distance between the first inner layer side region and the interface between the inner layer and the first side region is less than W / 10 or less than 40 μm; The distance between the second inner layer side region and the interface between the inner layer and the second side region is less than W / 10 or less than 40 μm; as well as The inner middle region is sandwiched between the first inner layer side region and the second inner layer side region. In the cross-section, the dielectric layer at the center of the thickness direction of the inner intermediate region contains particles with holes as dielectric particles. In the cross-section, the dielectric layer at the center of the thickness direction of at least one of the first inner layer side region and the second inner layer side region contains particles with holes as dielectric particles. In the cross section, the ratio of the number of holes among the dielectric particles at the center of the thickness direction of at least one of the first inner layer side region and the second inner layer side region, Wn / WN, is greater than the ratio of the number of holes among the dielectric particles at the center of the thickness direction of the inner layer middle region, Cn / CN.
2. The multilayer ceramic capacitor according to claim 1, wherein, In the cross section, the ratio of the number of holes among the dielectric particles at the center of the thickness direction of the inner layer intermediate region, Cn / CN, is 15% or more.
3. The multilayer ceramic capacitor according to claim 1 or 2, wherein, In the cross section, the ratio of the number of holes among the dielectric particles at the center of the thickness direction of at least one of the first inner layer side region and the second inner layer side region, Wn / WN, is 25% or more.
4. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The average pore size of the hole is greater than 10 nm and less than 30 nm.
5. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The average particle size of the dielectric particles is greater than 130 nm and less than 300 nm.
6. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The thickness of the dielectric layer is greater than 0.40 μm and less than 0.50 μm.
7. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The thickness of the dielectric layer is greater than 0.40 μm and less than 0.45 μm.
8. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The thickness of the internal electrode layer is greater than 0.30 μm and less than 0.40 μm.
9. The multilayer ceramic capacitor according to claim 1 or 2, wherein, The thickness of the internal electrode layer is greater than 0.30 μm and less than 0.35 μm.
Citation Information
Patent Citations
Dielectric ceramic composition and multilayer ceramic capacitor
JP2017178686A
Multilayer ceramic capacitor
CN101346784A
High density three-dimensional integrated capacitors
CN103348442A